Antiviral and Virucidal Activities against Arenaviruses of Zinc-Finger Active Compounds - Garcia, Cybele (2016)
Fifteen antiretroviral Zn-finger active compounds with diverse chemical structures, including azoic compounds, hydrazide derivatives, disulfide-based reagents and others, were screened in vitro against Junin virus (JUNV), the etiological agent of Argentine hemorrhagic fever, by a virus yield inhibition assay in Vero cells. Cytotoxicity was evaluated simultaneously by the MTT method. From the total of compounds, three were totally inactive as antivirals, nine presented moderate anti JUNV-activity and three were truly active with EC50 (effective concentration 50%) values in the range 6.5-9.3 µM and selectivity indices greater than 10. The most active inhibitors, named NSC20625, 3-7 and 2-71, demonstrated a broad range of action against arenaviruses, including several attenuated and pathogenic strains of JUNV as well as the antigenically related Tacaribe virus (TACV) and Pichinde virus (PICV). The direct treatment of JUNV and TACV virions with the compounds has shown two types of behavior: the aromatic disulfide NSC20625 was a very potent virucidal agent, whereas the other two compounds exhibited moderate or negligible virus inactivating properties.